2013
DOI: 10.2478/s11535-013-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of the Lithuanian wolf population

Abstract: Lithuanian wolves form part of the larger Baltic population, the distribution of which is continuous across the region. In this paper, we evaluate the genetic diversity of the Lithuanian wolf population using mitochondrial DNA analysis and 29 autosomal microsatellite loci. Analysis of the mtDNA control region (647 bp) revealed 5 haplotypes distributed among 29 individuals and high haplotype diversity (0.658). Two haplotypes were distributed across the country, whilst the others were restricted to eastern Lithu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
2
6
0
1
Order By: Relevance
“…In Finland [77,78,79] and Lithuania [80], where hunting pressure is low and immigration moderate, no population structuring has been observed. Therefore, on the basis of immigration alone, the much smaller territory of Estonia and Latvia might be expected to exhibit no population structuring at all.…”
Section: Discussionmentioning
confidence: 99%
“…In Finland [77,78,79] and Lithuania [80], where hunting pressure is low and immigration moderate, no population structuring has been observed. Therefore, on the basis of immigration alone, the much smaller territory of Estonia and Latvia might be expected to exhibit no population structuring at all.…”
Section: Discussionmentioning
confidence: 99%
“…The Baltic wolf population is distributed throughout Estonia (200–260), Latvia (200–400), Lithuania (∼300) and north‐eastern Poland (270–360), comprising 900–1400 animals in total. As in other parts of Europe, the Baltic wolf population experienced near‐extermination in the 1970s and 1980s (Jędrzejewski et al., ; Baltrūnaitė, Balčiauskas & Åkesson, ), leaving signs of genetic bottlenecks in wolves from Estonia, Latvia (Hindrikson et al., ; Plumer et al., ) and neighbouring Russia (Sastre et al., ). In general, the Baltic population exhibits relatively high levels of heterozygosity compared with many other European wolf populations (Jędrzejewski et al., ; Baltrūnaitė et al., ; Czarnomska et al., ; Hindrikson et al., ).…”
Section: Genetic Patterns Of European Wolf Populations Revealed By DImentioning
confidence: 99%
“…As in other parts of Europe, the Baltic wolf population experienced near‐extermination in the 1970s and 1980s (Jędrzejewski et al., ; Baltrūnaitė, Balčiauskas & Åkesson, ), leaving signs of genetic bottlenecks in wolves from Estonia, Latvia (Hindrikson et al., ; Plumer et al., ) and neighbouring Russia (Sastre et al., ). In general, the Baltic population exhibits relatively high levels of heterozygosity compared with many other European wolf populations (Jędrzejewski et al., ; Baltrūnaitė et al., ; Czarnomska et al., ; Hindrikson et al., ). Moreover, a cryptic genetic structuring has been found in the Estonian–Latvian part of this population (Hindrikson et al., ) and the authors proposed that the four genetic groups identified reflect recent population bottlenecks, severe hunting pressure and immigration.…”
Section: Genetic Patterns Of European Wolf Populations Revealed By DImentioning
confidence: 99%
See 1 more Smart Citation
“…Metaforiniai terminai -perkeltinės reikšmės žodžiai ar viena iš sudėtinių pastovaus žodžių junginio dalių, turinti tokią (perkeltinę) reikšmę, kuria įvardijama speciali mokslo, technikos, meno ar kitos visuomenės gyvenimo srities sąvoka (Baltrūnaitė 1998). Metaforiniai terminai priklauso kalbinių (leksinių, leksikalizuotų, negyvų, mirusių, nominatyvinių ir kt.)…”
Section: Metaforiniai Terminaiunclassified